Using the results of intellectual activity in the banking sphere - I. A. Belousova; A. A. Dulyov (Путеводитель предпринимателя)
The article discusses issues related to the implementation of innovative and information technologies in the process of functioning of banking institutions. The analysis of the main directions of the use of modern technologies is outlined, their advantages and main problems arising from the application of innovations in the processes of providing banking services and operations are revealed. Based on the study, the main areas of use of the results of intellectual activity in the banking sector were identified. The directions of introduction of innovative financial technologies in the process of providing banking services are indicated, which will allow banks to overcome competition with other participants of the financial market and increase their efficiency, as well as accelerate Russia’s transition to the digital economy.